Mdm2 promotes Cdc25C protein degradation and delays cell cycle progression through the G2/M phase - Giono, Luciana Eugenia (2017)
Upon different types of stress, the gene encoding the mitosis-promoting phosphatase Cdc25C is transcriptionally repressed by p53, contributing to p53’s enforcement of a G2 cell cycle arrest. In addition, Cdc25C protein stability is also decreased following DNA damage. Mdm2, another p53 target gene, encodes a ubiquitin ligase that negatively regulates p53 levels by ubiquitination. Ablation of Mdm2 by siRNA led to an increase in p53 protein and repression of Cdc25C gene expression. However, Cdc25C protein levels were actually increased following Mdm2 depletion. Mdm2 is shown to negatively regulate Cdc25C protein levels by reducing its half-life independently of the presence of p53. Further, Mdm2 physically interacts with Cdc25C and promotes its degradation through the proteasome in a ubiquitin-independent manner. Either Mdm2 overexpression or Cdc25C downregulation delays cell cycle progression through the G2/M phase. Thus, the repression of the Cdc25C promoter by p53, together with p53-dependent induction of Mdm2 and subsequent degradation of Cdc25C, could provide a dual mechanism by which p53 can enforce and maintain a G2/M cell cycle arrest.